2013
DOI: 10.1134/s1547477113050087
|View full text |Cite
|
Sign up to set email alerts
|

On the heavy elements content of sediments and rocks from two semiclosed ecosystems: Proglacial Lake Balea (Fagara Mountains) and Crater Lake St. Ana (Harghita Mountains)

Abstract: The content of seven heavy elements (natural Sc and Cr, Co, As, Sb, Br and Se as possible pollutants) was determined by the Neutron Activation Analysis (NAA) in 29 samples of sediments and surrounding rocks collected from proglacial Lake Bå alea (Få agå aras Mountains) and crater St. Ana Lake (Harghita Mountains) to estimate the degree of anthropogenic pollution, as well as the sediments provenance. Consequently, we have found that, within experimental uncertainties, the content of the considered elements in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…One of the anthropogenic sources of chromium is the metallurgical industry (Maas et al, 2010). The average content of chromium determined from sediments extracted from St. Anna volcanic lake near Mohoș peatland is 31 ± 3 mg/kg, with a standard deviation of 29 ± 10 (Duliu et al, 2013), and from andesites and dacites taken from the Ciomadul volcanic structure, Seghedi et al (1986) give a chromium content of 11–47 mg/kg. In a previous study by Pantelica et al (1997), the concentration of chromium in the Poiana Stampei peatland is revealed to be of 9.7 ± 0.5 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…One of the anthropogenic sources of chromium is the metallurgical industry (Maas et al, 2010). The average content of chromium determined from sediments extracted from St. Anna volcanic lake near Mohoș peatland is 31 ± 3 mg/kg, with a standard deviation of 29 ± 10 (Duliu et al, 2013), and from andesites and dacites taken from the Ciomadul volcanic structure, Seghedi et al (1986) give a chromium content of 11–47 mg/kg. In a previous study by Pantelica et al (1997), the concentration of chromium in the Poiana Stampei peatland is revealed to be of 9.7 ± 0.5 mg/kg.…”
Section: Discussionmentioning
confidence: 99%